End tidal CO2 and cerebral oximetry for the prediction of return of spontaneous circulation during cardiopulmonary resuscitation. (June 2019) - Engel, Thomas W.; Thomas, Craig; Medado, Patrick; Bastani, Aveh; Reed, Brian; Millis, Scott; O'Neil, Brian J.
Abstract: Background: End Tidal CO2 (ETCO2 ) is a reasonable predictor of Return of Spontaneous Circulation (ROSC) in cardiac arrest (CA), though with many limitations. Cerebral Oximetry (CerOx) non-invasively measures brain O2 saturation and correlates with flow. Objectives: This study compares ETCO2 and CerOx for ROSC prediction during both out of hospital (OHCA) and emergency department cardiac arrests (EDCA). Methods: We conducted a prospective study on CA patients resuscitated in the ED. ETCO2 and CerOx simultaneously measured during ED CPR. Data was analyzed with logistic regression modeling and area under the curve (AUC). Results: 176 patients were analyzed, 66.7% were witnessed, 52.8% had bystander CPR. EMS alert to ED arrival was 27.0 ± 10.6 min. Initial rhythm was 31.8% asystole, 27.8% PEA, 25.6% VF/VT with 26.1% achieving ROSC. AUC predictors of ROSC were: last 5 min trend [CerOx = 0.82 ; ETCO2  = 0.74], delta first to last [CerOx = 0.86 ; ETCO2  = 0.73], the penultimate minute [CerOx = 0.81 ; ETCO2  = 0.76], and final minute [CerOx = 0.89 ; ETCO2  = 0.77]. AUC comparison of simultaneous measurements (n = 125) revealed: last 5 min trend [CerOx = 0.80 ; ETCO2  = 0.79], delta first to last [CerOx = 0.83 ; ETCO2  = 0.75], penultimate minute [CerOx = 0.83 ETCO2  = 0.74], and final minute [CerOx = 0.89 ; ETCO2 = 0.75]. Conclusions: Our data shows, both ETCO2 and rSO2 are good predictors of ROSC. We found CerOx superior to ETCO2 in predicting ROSC.